An intelligent analysis method of security and stability control strategy based on the knowledge graph - Wen, Bo; Li, Hengxuan; Zhang, Junhao; Han, Qingqing; Ding, Zehua (Frontiers in Energy Research, 2023)
The security and stability control system is the guarantee of the safe and stable operation of the power grid. With the increasing scale of the distributed new energy access to the power grid, the security and stability control strategy of the power grid is becoming more complex, and it is in-creasingly important to correctly analyze and implement the security and stability control strategy. As an important device of the security and stability control system, whether the security and sta-bility control device can correctly implement the security and stability control strategy is an im-portant condition for the safe and stable operation of the power grid. In order to ensure the cor-rectness of the security and stability control strategy implemented by the stability control device, it is necessary to analyze the security and stability control strategy in detail. Therefore, this paper proposes an intelligent analysis method of the security and stability control strategy based on knowledge graph, and uses artificial intelligence technology to model and manage the the security and stability control strategy, so as to solve the problems of low efficiency and incomplete strategy detection of current stability control devices. Firstly, this paper introduces the ontology design method of the security and stability control strategy based on knowledge graph, combines the characteristics and applications of knowledge graph, designs a clear structured knowledge network by combing the relationship between the elements of the strategy, and then analyzes the automatic construction technology of the graph to realize the human-computer interaction functions such as assistant decision-making, strategy reasoning and intelligent search based on the knowledge graph, Finally, the prospect and challenge of applying knowledge graph to the security and stability control strategy analysis are summarized.